2016
DOI: 10.1016/j.colsurfb.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

PLLA/ZnO nanocomposites: Dynamic surfaces to harness cell differentiation

Abstract: Graphical abstract2 Highlights  Biodegradable poly(L-lactide) matrix loaded with ZnO nanorods. Dynamic presentation of nanorods triggered by PLLA degradation. Changes in surface properties as a function of time control cell behaviour. Nanorods exposure promotes cell differentiation.3 Keywords: PLLA, ZnO nanoparticle, C2C12 myoblast, nanocomposite, cell differentiation AbstractThis work investigates the effect of the sequential availability of ZnO nanoparticles, (nanorods of ~ 20 nm) loaded within a degrada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Our group has previously shown that PLLA hydrolytic degradation preferably occurs at the PLLA–ZnO interface, suggesting that the formation of surface COOH groups upon hydrolysis may be faster when in the presence of ZnO nanoparticles because they are able to speed up the whole hydrolytic process . Therefore, the incorporation of ZnO nanoparticles into PLLA matrix is seen as an efficient approach to improve the efficiency of the surface modification process (hydrolysis) and obtain biocompatible materials with tunable surface properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has previously shown that PLLA hydrolytic degradation preferably occurs at the PLLA–ZnO interface, suggesting that the formation of surface COOH groups upon hydrolysis may be faster when in the presence of ZnO nanoparticles because they are able to speed up the whole hydrolytic process . Therefore, the incorporation of ZnO nanoparticles into PLLA matrix is seen as an efficient approach to improve the efficiency of the surface modification process (hydrolysis) and obtain biocompatible materials with tunable surface properties.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have shown that PLLA/ZnO system shows promising properties for the packaging and biomedical field . ZnO is approved by the American Food and Drug Administration, which shows useful UV‐shielding properties when incorporated into biopolymers, and is able to prompt hydrolytic degradation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of biocompatibility, biodegradability and the fact that it is an immunologically inert polymer, the PLLA is suitable for tissue engineering applications . In order to improve mechanical properties or insert specific functionalities in PLA or PLLA for tissue engineering in general, researchers have been investigating the incorporation of distinct nanostructured materials into this biopolymeric matrix …”
Section: Introductionmentioning
confidence: 99%
“…18 In order to improve mechanical properties or insert specific functionalities in PLA or PLLA for tissue engineering in general, researchers have been investigating the incorporation of distinct nanostructured materials into this biopolymeric matrix. 4,[17][18][19][20][21][22] Among the distinct applications of biopolymers in tissue engineering, one of significant interest is related to the dental area. In this field, a problem of major concern is the periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…As compared to heparin functionalized biointerface, the fabricated biointerface contained exposed RGD motif which could efficiently bind with cell surface to improve cell affinity to the engineered interface. Moreover, unlike chemical synthetic molecules or inorganic materials, bFGF is a natural peptide which is biocompatible with biological tissues . In addition to its role in efficiently promoting cell differentiation, bFGF has also been recognized to function in preventing nerve cell death and promoting nerve recovery from nerve injuries; therefore, the cooperative effect of PRGD/bFGF could also be used to functionalize biointerface on artificial conduits for nerve regeneration .…”
mentioning
confidence: 99%